2010
DOI: 10.1128/jcm.00646-10
|View full text |Cite
|
Sign up to set email alerts
|

New Genotypes within Respiratory Syncytial Virus Group B Genotype BA in Niigata, Japan

Abstract: Phylogenetic analysis of respiratory syncytial virus (RSV) group B genotype BA strains from the 2002-2003 to 2009-2010 seasons collected in Niigata, Japan, revealed four distinct clusters, designated new BA genotypes BA7, BA8, BA9, and BA10. These new genotypes were not associated with large outbreaks in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
144
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(171 citation statements)
references
References 19 publications
18
144
2
1
Order By: Relevance
“…Reference sequences (BA/100/04, BA/524/04, BA/354/04, and BE/46/03) were downloaded from GenBank (http://www.ncbi.nlm.nih.gov/). The G-protein gene sequences newly reported in this paper were deposited in the DDBJ database, and others were reported previously (7,23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference sequences (BA/100/04, BA/524/04, BA/354/04, and BE/46/03) were downloaded from GenBank (http://www.ncbi.nlm.nih.gov/). The G-protein gene sequences newly reported in this paper were deposited in the DDBJ database, and others were reported previously (7,23).…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that the newly identified genotype NA2 of HRSV-A caused the outbreak in the 2006-2007 season, while emerging HRSV-B genotypes did not cause an outbreak in the community (7,26). In conjunction with data from previous molecular epidemiological studies, we undertook the present study to analyze the characteristics of reinfections in relation to HRSV genetic diversity among children with repeated HRSV infections in Japan.…”
mentioning
confidence: 99%
“…The G protein is one of the targets of host immune response and thus a vaccine candidate. hRSV group B strains have been classified into 13 reported genotypes GB1, GB2, GB3, GB4, SAB1, SAB2, SAB3, SAB4, URU1, URU2, JAB1, CB1 and BA [5,8,9,21,23,25]. The BA genotype has 60 nucleotide duplication in the second hypervariable region of the G protein gene.…”
Section: Introductionmentioning
confidence: 99%
“…Co-circulation of multiple subtypes and genotypes has been frequently reported in a single RSV season, although usually one genotype is predominant (189-194, 196-202, 204-209). Within a population the prevalent RSV subtype and genotype has been reported to shift every few years (190,193,194,199,201,205,206,209), most likely due to shortlived, specific herd immunity (210). Genotype replacement has also been observed, where the emergence of a new genotype has appeared to have had a selective advantage, resulting in the replacement of previous lineages by the new genotype in a population (194,205,206,209).…”
Section: Genetic Diversitymentioning
confidence: 96%
“…A 60 nucleotide duplication event in HVR2 of an RSV-B strain was first observed in 1999 in Buenos Aires (genotype BA) (211) and rapidly spread worldwide (212). At least twelve BA sub-genotypes have now been described (194,206,212,213), and they are consistently identified as the predominant RSV-B strains in seasonal epidemics (188, 189, 191-196, 200, 202, 206, 208, 209, 214). In RSV-A, global patterns of RSV epidemics demonstrate that in the mid 1990s genotypes GA2 and GA7 were prevalent, with the emergence of GA5 and the divergence of GA2 into NA1 and NA2 in the 2000s (188,194,201).…”
Section: Genetic Diversitymentioning
confidence: 99%